Pengaruh Pola Asuh terhadap Keterampilan Sosial: Analisis Studi Literatur - Azkia Sopiatunnisa; Nida Nur Azizah; Sri Mulyeni (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the influence of parenting styles on the development of social skills in early adolescence. The method used was a literature review. Researchers reviewed and synthesized the results of relevant previous studies, sourced from scientific journals and credible digital databases. The analysis results show a consistent relationship between the type of parenting style and the quality of social skills. Democratic parenting has been shown to make a significant positive contribution to communication skills, empathy, cooperation, emotional control, and adjustment in social environments. Adolescents raised with this parenting style tend to have better self-confidence and are able to build healthy social interactions at school and in the community. Conversely, authoritarian and permissive parenting styles tend to have less beneficial impacts. This is characterized by the emergence of social anxiety, low initiative, difficulty adhering to social norms, and limitations in establishing interpersonal relationships. These findings emphasize the crucial role of parents in shaping the social competence of early adolescents. The study concludes that implementing a balanced, consistent, and communicative parenting style is a key factor in supporting the development of social skills. Collaboration between the family and the educational environment needs to be strengthened.